Pengembangan Lembar Kerja Peserta Didik (LKPD) Terintegrasi Al-Qur’an dan Hadits Pada Materi Pertumbuhan dan Perkembangan Hewan Dan Manusia - Nanda Putri, Melisa; Maidhaturrofiah; Azzahra, Masayu; Hiras Habisukan, Ummi; Asnilawati (Universitas Cokroaminoto Palopo, 2025)
This study aims to develop a Student Worksheet (LKPD) product integrated with the Qur'an and Hadith on the material of animal and human growth and development, and to determine the level of validity and practicality. This research method uses R & D (Reserch and Development and was implemented at SMA Palembang. The research subjects consisted of 9 students and 2 biology teachers. The instruments used were student response questionnaires and teacher practicality questionnaires. Based on the analysis of research data, the validity results by the validator were 94.66%, 97.33%, 97.33%, 96.00%, and the students' responses with an average of 94.95% were in the very practical category, while the teachers' practicality with an average of 90.66% was in the very practical category. Based on these results, LKPD was declared very practical and very valid to be used as biology teaching materials that integrate Islamic values ​​and scientific concepts.